Blast disease: A threat to finger millet cultivation - Thakur, Swagata (Indian Farming, 2023)
Finger millet (Eleusine coracana L. Gaertn), commonly known as Ragi or Mandua is a nutritionally important coarse cereal and a traditional crop widely grown under varied agroclimatic regions, especially in semi-arid areas of African and Asian countries and plays a key role in the livelihood of small-holding farmers in these regions. Though finger millet is one of the hardiest crops, it is affected by a good number of diseases, and the blast disease caused by Pyricularia grisea is the most destructive disease in which seedlings may die under epidemic conditions, and broken pedicels and empty fingers may result in mature plants causing leaf, neck and finger blast, respectively. An integrated management approach should be undertaken to tackle the disease and to increase the yield towards potentiality. This article aims to provide the farmers’ and researchers’ society with concise knowledge about this devastating disease of finger millet for its early detection and mitigation.